IMPLEMENTATION OF CAT STRETCH EXERCISE AND COUNTER PRESSURE TO REDUCE MENSTRUAL PAIN IN ADOLESCENT GIRLS AT THE ISLAMIC BOARDING SCHOOL OF CAHAYA MADINAH, SOUTH TANGERANG, BANTEN - Desmawati, Desmawati; Pamungkas, Eny Dewi; Noer, Sirajudin; Sudiharto, Sudiharto; Faradillah, Kiki Rezki; Widyatnoko, Dodhi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Menstrual pain or dysmenorrhea is problem in adolescent girls. Menstrual pain also be a reason for the decreased activity of women during menstruation, including female students at the Pesantren Yatim Cahaya Madinah, South Tangerang, Banten. The objective of this community service is to address menstrual pain in adolescents through several methods including: 1) providing education on nonpharmacological therapy to reduce menstrual pain, addressing the lack of information, knowledge, and understanding related to menstruation; 2) implementing Cat Strecth Exercise dan Counter Pressure for menstrual pain in adolescent girls; 3) adopting positive lifestyle changes to decrease menstrual pain, supervising, and reevaluating programs. Adolescents are able to remain productive during menstruation, implement Cat Strecth Exercise dan Counter Pressure, and stay healthier and more productive even while menstruating. The results of this intervention have proven effective in reducing menstrual pain through non-pharmacological therapy, leading to healthier and more sustainable productivity for adolescent girls. Those who initially experienced severe pain (scale 6), causing distress and lower abdominal cramps during menstruation that often reduced their quality of life—along with discomfort affecting their physical and mental well-being, often accompanied by nausea, vomiting, abdominal pain, breast pain, rectal swelling, and diarrhea—reported a reduction in menstrual pain to a scale of 3 after this intervention.